Case study: characterization of solid waste management system in metallurgic companies of Joaçaba/SC - Zorzi, Juliana Luiza; Vanin, Adriana Biasi; Azzolini, José Carlos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
The development of a country is intimately linked to the industrial development that is responsible for wealth generation, jobs and income, however, it is followed by serious environmental impacts caused by production and incorrect disposal of waste. The present research aimed to characterize the solid waste management system in metallurgic companies from Joaçaba/SC. For this, a research instrument was applied containing twelve open questions for the heads of seven companies. The questions included the identification of solid waste generated in the production process and the disposal method, as well as information about environmental licensing and reverse logistic. The research showed that only one company has an environmental management system and has a better understanding about its environmental responsibilities, both the management of waste generated by the production process and the importance of preserving the environmental.